Secular changes in relationships between plate-tectonic and mantle-plume engendered processes during Precambrian time - Mints Mikhail V.; Eriksson Patrick G. (Федеральное государственное бюджетное учреждение науки Институт земной коры Сибирского отделения Российской академии наук, 2016)
Paradoxically, the lists of "proxies" of both plateand plume-related settings are devoid of even a mention of the high-grade metamorphic rocks (granulite, amphibolite and high-temperature eclogite facies). However, the granulite-gneiss belts and areas which contain these rocks, have a regional distribution in both the Precambrian and the Phanerozoic records. The origin and evolution of the granulite-gneiss belts correspond to the activity of plumes expressed in vigorous heating of the continental crust; intraplate magmatism; formation of rift depressions filled with sediments, juvenile lavas, and pyroclastic flow deposits; and metamorphism of lower and middle crustal complexes under conditions of granulite and high-temperature amphibolite facies that spreads over the fill of rift depressions also. Granulite-gneiss complexes of the East European Craton form one of the main components of the large oval intracontinental tectonic terranes of regional or continental rank. Inclusion of the granulite-gneiss complexes from Eastern Europe, North and South America, Africa, India, China and Australia in discussion of the problem indicated in the title to this paper, suggests consideration of a significant change in existing views on the relations between the plateand plume-tectonic processes in geological history, as well as in supercontinent assembly and decay. The East European and North American cratons are fragments of the long-lived supercontinent Lauroscandia. After its appearance at ~2.8 Ga, the crust of this supercontinent evolved under the influence of the sequence of powerful mantle plumes (superplumes) up to ~0.85 Ga. During this time Lauroscandia was subjected to rifting, partial breakup and the following reconstruction of the continent. The processes of plate-tectonic type (rifting with the transition to spreading and closing of the short-lived ocean with subduction) within Lauroscandia were controlled by the superplumes. Revision of the nature of the granulite-gneiss complexes has led to a fundamental new understanding of: a more important role than envisaged previously for mantle-plume processes in the juvenile additions to the continental crust, especially during the Neoarchaean-Proterozoic; the existence of the supercontinent Lauroscandia from ~2.80 to 0.85 Ga; the leading role of mantle plumes in the interaction of plateand plume-tectonics in the Neoarchaean-Proterozoic history of Lauroscandia and perhaps of the continental crust as a whole. We propose that the evolution of the geodynamic settings of the Earth's crust origin can be represented as a spiral sequence: the interaction of mantle-plume processes and embryonic microplate tectonics during the Palaeo-Mezoarchaean (~3.8-2.8 Ga) → plume-tectonics and local plume-driven plate-tectonics (~2.80-0.55 Ga) → Phanerozoic plate tectonics along with a reduced role of mantle plumes.
Keywords: PRECAMBRIAN; PLATE-TECTONICS; PLUME-TECTONICS; GRANULITE-GNEISS BELTS; SUPERCONTINENT; INTRACONTINENT OVAL OROGEN; ДОКЕМБРИЙ; ТЕКТОНИКА ПЛИТ; ТЕКТОНИКА ПЛЮМОВ; ГРАНУЛИТО-ГНЕЙСОВЫЙ ПОЯС; СУПЕРКОНТИНЕНТ; ВНУТРИКОНТИНЕНТАЛЬНЫЙ ОВАЛЬНЫЙ ОРОГЕН; Докембрий; Precambrian